PEMANFAATAN LUMI EDUCATION PADA MATERI PANTUN BERBASIS ADAT DALIHAN NA TOLU DI SMK - Yulira Putri Nirwana Boang Manalu; Ika Septiana; Nazla Maharani Umaya (Fon: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2026)
ABSTRAK: Penelitian ini bertujuan mendeskripsikan pemanfaatan LUMI Education sebagai media pembelajaran digital interaktif untuk materi pantun berbasis adat Dalihan Na Tolu di SMK Maranatha Sidikalang, Kabupaten Dairi, Sumatera Utara. Penelitian menggunakan pendekatan kualitatif deskriptif dengan triangulasi data observasi kelas, angket Likert terhadap 24 siswa kelas XI Seni Musik, dan wawancara semi-struktural dengan 5 siswa purposif serta 2 guru Bahasa Indonesia. Analisis data mengikuti model Miles dan Huberman. Hasil penelitian menunjukkan bahwa LUMI Education dapat menghasilkan pembelajaran yang interaktif, kontekstual, dan berpusat pada siswa. Siswa menunjukkan respons positif yang tinggi dengan rata-rata skor angket 3,78 (skala 4), khususnya terhadap relevansi nilai Dalihan Na Tolu (skor 3,83). LUMI Education efektif meningkatkan minat, pemahaman struktur pantun, serta menumbuhkan rasa menghargai budaya daerah. Simpulannya, integrasi LUMI Education dengan kearifan lokal merupakan strategi pembelajaran yang inovatif dan efektif.  Implikasi penelitian ini menegaskan pentingnya pengembangan media digital berbasis budaya lokal untuk memperkuat literasi, karakter, dan identitas peserta didik, serta mendorong inovasi pembelajaran Bahasa Indonesia yang adaptif terhadap perkembangan teknologi. KATA KUNCI: LUMI Education; Pantun; Dalihan Na Tolu; Media Pembelajaran Digital; Kearifan Lokal   APPLICATION OF THE LUMI EDUCATION MODEL IN THE CONTEXT OF PANTUN MATERIAL BASED ON THE DALIHAN NA TOLU CUSTOMS IN VOCATIONAL SCHOOLS   ABSTRACT: The objective of research is to describe the use of LUMI Education as an interactive digital learning medium for Dalihan Na Tolu traditional pantun material at SMK Maranatha Sidikalang, Dairi Regency, North Sumatra. The empirical study employed a descriptive qualitative methodology, utilizing triangulation of classroom observation data, a Likert questionnaire administered to 24 students enrolled in the 11th grade Music class, and semi-structured interviews with 5 purposively selected students and 2 Indonesian language teachers. The data analysis was conducted according to the Miles and Huberman model. The findings indicated that LUMI Education is capable of facilitating interactive, contextual, and student-centered learning. The study revealed a predominantly favorable response from the student participants, with an average questionnaire score of 3.78 on a scale of 4. Notably, the relevance of Dalihan Na Tolu values received a particularly high rating, with a score of 3.83. The implementation of LUMI Education yielded significant improvements in student interest, comprehension of pantun structure, and the cultivation of an appreciation for local culture. In sum, the integration of LUMI Education with local wisdom has been demonstrated to be an innovative and effective learning strategy. The implications of this study underscore the importance of developing local culture-based digital media to strengthen the literacy, character, and identity of students, as well as to encourage innovation in Indonesian language learning that is adaptive to technological developments. KEYWORDS: LUMI Education; Pantun; Dalihan Na Tolu; Digital Learning Media; Local Wisdom